A Review and Management of the 'Anugerah' Computer Shop Application Based on Android and iOS Mobile - Irmayani, Deci; Siregar, Zakia El Husna; Sari, Mila Nirmala (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
The need for e-commerce is primarily for business actors such as Anugerah PC, which is engaged in PC repair and sales services. Since the COVID-19 pandemic devastated the industrial world, more time has passed, and ideas have emerged to build digital-based applications, even mobile-based ones. Digital-based, for example, is the existence of an application website that is very user-friendly but needs development, such as the development of an Android mobile or iOS mobile application, depending on the operating system used by the mobile device. This research is one of the answers to this problem. Anugerah PC built a mobile-based application to answer the challenges in the current 5.0 industrial revolution era. So, with this application, Anugerah stores can get a lot of followers, especially customers who are ready to buy at Anugerah stores. Anugerah PC shop can be the best in sales through e-commerce with a very flexible Android Mobile system.